Development and characterization of hybrid polymer composite materials with reinforcement of glass/carbon fibers for enhanced mechanical properties: an experimental and numerical approach - Singh M.; Yadav R.; Kumar R.; Dodla S.; Gautam R.K. (My University, 2025)
Composite materials, particularly fiber-reinforced plastics (FRP), are used in aerospace and automotive industries due to their desirable properties and surpassing traditional metals in various applications. Researchers are countering the drawbacks of using a single fiber type in FRP by creating hybrid composites that combine different fibers in a single matrix. These hybrids harness the cost-effectiveness and corrosion resistance of glass fibers alongside the strength and stiffness of carbon fibers, resulting in a balanced combination of properties for various applications. Tensile tests were performed according to the ASTM D3039 standard, with a 2 mm/min strain rate. The results showed that increasing the carbon fiber percentage (6.56%, 13.79%, and 21.07%) led to significant improvements in the tensile strength of the hybrid composites (34.18%, 55.44%, and 85.40% higher than glass fiber composites). However, changing the stacking sequence did not significantly affect tensile strength, indicating its insignificance in this regard. Numerical simulations were conducted to validate the experimental results, and the errors between experimental and numerical data were below 10% for various stacking sequences. These discrepancies were attributed to factors such as fiber waviness, which resulted in heterogeneous property distribution within the composites, and the manufacturing process used for creating the hybrid composites. Scanning electron microscope analysis was also performed to study the failure modes on the fracture surface of the tensile-tested specimens. © 2024 The Textile Institute.